Challenges in Developing Ventilation and Indoor Air Quality Standards: The Story of ASHRAE Standard 62 - Persily, Andrew (Build Environ, 2015)
Building ventilation has long been recognized for its role in occupant health, comfort and productivity, with some of the first recommendations on building ventilation rates published in the 19(th) century. These recommendations were subsequently transformed into more rigorous standards and guidance in the 20(th) century, with the first version of ASHRAE Standard 62 published in 1973. Since that time, ventilation standards have been issued in several countries around the world and have dealt with an increasingly complex and challenging range of issues as research on indoor air quality and the state of knowledge of building performance have progressed. This paper reviews and discusses some of the issues that have been addressed in the development of ventilation standards in recent years using the development of ASHRAE Standard 62 as context, including: the scientific bases for ventilation requirements, perceived indoor air quality, contaminant sources from occupants and the building, outdoor air quality, airborne contaminant limits, indoor carbon dioxide concentrations, environmental tobacco smoke, and performance-based design. Issues that are expected to be dealt with as Standard 62 and other standards are developed into the future are also reviewed.